Epidemiological and clinical characteristics of Peruvian patients with mpox: A systematic review and meta-analysis - Darwin A. León-Figueroa; Edwin Aguirre-Milachay; Milagros Diaz-Torres; Virgilio E. Failoc-Rojas; Rodrigo Camacho-Neciosup; Abel Eduardo Chávarry Isla; Mario J. Valladares-Garrido (PLoS ONE, 2025)
Background Mpox has become a public health problem due to its rapid evolution and clinical variability. In Latin America, Peru ranks fifth in terms of the number of cases. The main objective of this study is to determine the epidemiological and clinical characteristics of Peruvian patients diagnosed with mpox, providing a detailed view of the situation of this affected population. Methods A systematic review and meta-analysis of studies on mpox in Peru was carried out using ten databases and search tools (PubMed, Scopus, Web of Science, Embase, ScienceDirect, Google Scholar, Virtual Health Library, Scielo, Dimensions, and Epistemonikos) until August 22, 2024. The MeSH (Medical Subject Headings) terms used in the search were “mpox” and “Peru”, combined with the logical operators AND and OR. Study quality was assessed using the Joanna Briggs Institute (JBI) assessment tool, and pooled estimates were generated using random-effects meta-analysis. Heterogeneity was assessed using the I² statistic. Statistical analysis was performed in R version 4.2.3, and the study was registered in PROSPERO (CRD42024582854). Results A total of 150 articles were evaluated, of which 9 studies were included: four retrospective observational studies, four case series, and one case report, covering a total of 3960 Peruvian patients with mpox. The quality of the studies was moderate. The combined results show that 97% (95% CI: 96–98%; 3804 participants; 4 studies; I2 = 24%, p = 0.27) of the patients were male, 63% (95% CI: 57–68%; 2366 participants; 4 studies; I2 = 66%, p = 0.03) had HIV (human immunodeficiency virus), and 91% (95% CI: 83–97%; 2019 participants; 4 studies; I2 = 90%, p < 0.01) of these were receiving antiretroviral therapy. In addition, 61% (95% CI: 46–75%; 2295 participants; 4 studies; I2 = 95%, p < 0.01) identified as homosexual, and 17% (95% CI: 09–26%; 702 participants; 4 studies; I2 = 91%, p < 0.01) had a history of syphilis. The most common clinical manifestations were skin lesions (88%; 95% CI: 79–94%; 3114 participants; 4 studies; I2 = 92%, p < 0.01), lymphadenopathy (83%; 95% CI: 25–100%; 3623 participants; 2 studies; I2 = 100%, p < 0.01), anogenital rash (72%; 95% CI: 65–79%; 2657 participants; 3 studies; I2 = 74%, p = 0.02), fever (67%; 95% CI: 59–76%; 2587 participants; 4 studies; I2 = 86%, p < 0.01), and headache (52%; 95% CI: 47–57%; 1962 participants; 3 studies; I2 = 60%, p = 0.08). Conclusion This systematic review provides a detailed overview on the epidemiology and clinical characteristics of Peruvian patients with mpox, highlighting a high prevalence in men and a remarkable association with HIV coinfection. The data highlight the vulnerability of the affected population and the importance of a multidisciplinary medical approach, with emphasis on early diagnosis of the most common symptoms. The findings support the implementation of prevention strategies tailored to the most vulnerable populations, especially those with HIV coinfection, and the conduct of longitudinal studies to better understand the disease.